Intranatal antigen injection as an experimental model of undifferentiated connective tissue dysplasia syndrome - Hryhorieva, Olena; Abrosimov, Yurii; Svitlytskyi, Andrii; Григор'єва, Олена Анатоліївна; Абросімов, Юрій Юрійович; Світлицький, Андрій Олександрович (Norway: Oslo, 2020)
The role of connective tissue in the functioning of organs and systems of the body is undeniable, because it performs many functions, participates in maintaining homeostasis, so disorders of connective tissue metabolism lead to a variety of structural changes in organs, contribute to the formation of secondary (associated) pathologies of internal organs and systems. Connective tissue dysplasia is a group of genetically heterogeneous and clinically polymorphic pathological conditions characterized by impaired connective tissue formation in the embryonic and postnatal periods, and also combines a number of genetic syndromes (Marfan, Ehlers-Danlos) and undifferentiated (non-syndromic) forms with multifactorial development mechanisms.